Genetic and mechanistic basis for APOBEC3H alternative splicing, retrovirus restriction, and counteraction by HIV-1 protease. Issue 1 (December 2018) - Ebrahimi, Diako; Richards, Christopher; Carpenter, Michael; Wang, Jiayi; Ikeda, Terumasa; Becker, Jordan; Cheng, Adam; McCann, Jennifer; Shaban, Nadine; Salamango, Daniel; Starrett, Gabriel; Lingappa, Jairam; et al.
Abstract Human APOBEC3H (A3H) is a single-stranded DNA cytosine deaminase that inhibits HIV-1. Seven haplotypes (I–VII) and four splice variants (SV154/182/183/200) with differing antiviral activities and geographic distributions have been described, but the genetic and mechanistic basis for variant expression and function remains unclear. Using a combined bioinformatic/experimental analysis, we find that SV200 expression is specific to haplotype II, which is primarily found in sub-Saharan Africa. The underlying genetic mechanism for differential mRNA splicing is an ancient intronic deletion [del(ctc)] within A3H haplotype II sequence. We show that SV200 is at least fourfold more HIV-1 restrictive than other A3H splice variants. To counteract this elevated antiviral activity, HIV-1 protease cleaves SV200 into a shorter, less restrictive isoform. Our analyses indicate that, in addition to Vif-mediated degradation, HIV-1 may use protease as a counter-defense mechanism against A3H in >80% of sub-Saharan African populations. Human APOBEC3H has several haplotypes and splice variants with distinct anti-HIV-1 activities, but the genetics underlying the expression of these variants are unclear. Here, the authors identify an intronic deletion in A3H haplotype II resulting in production of the most active splice variant, which is counteracted by HIV-1 protease.